Transaksi Peminjaman & Pengembalian Buku Pada SMA 3 Cikarang Utara Menggunakan Barcode Dengan Metode Waterfall - Suherman Suherman; Ramadhan Tirta (Jurnal SIGMA, 2022)
Application of information technology has now spread almost in all areas is no exception in the library. The need for information technology is closely linked to the role of libraries as a force in the preservation and dissemination of scientific and cultural information. The service and archiving of books data in the library that is manual resulting in slow service and less accurate information of existing book data, toovercome the above problems it requires a library automation system that is able to provide services in library transactions are fast, accurate and efficient. The purpose of this library automation system is to optimize library services in providing services both in lending and return transactions, new book data inputs as well as in book search. The library automation system is created by utilizing barcode scanners as a tool to assist in the process of all transactions in the library. Keywords:Automation, barcode, library